SEMIOTIC ANALYSIS ON FENTY BEAUTY’S FOUNDATION ADVERTISING POSTER AS A REPRESENTATIVE OF BEAUTY DIVERSITY - Rachma Prayudawardani, Azahra; Hadiati, Chusni; Muttaqin, Usep (LUNAR, 2023)
This research entitled "Semiotic Analysis on Fenty Beauty's Foundation Advertising Poster as a Representative of Beauty Diversity". This involves analyzing the Fenty Beauty foundation advertising poster employing the semiotic field. The descriptive qualitative approach was chosen in this research, and the aims of this research to identify the icon, index, and symbol in Fenty Beauty's foundation advertising poster, and to determine the relationship between signs and the beauty diversity issue in Fenty Beauty's foundation advertising poster. To figure out the answer, the researcher applies a semiotic theory by Charles Sanders Peirce to examine five Fenty Beauty foundation advertising posters. Purposive sampling was used as the data gathering strategy to assess the eight Fenty Beauty foundation advertising posters. Based on the results of this research, the messages contained in all posters can influence individuals to purchase Fenty Beauty's foundation. Fenty Beauty attempts to bring out the theme of beauty diversity in their advertising posters by including models with various skin tones, ethnicities, and religions. Fenty Beauty creates a revolution and reduces discrimination in the cosmetics industry by developing fifty colors of foundation.